Life: Computational Genomics Applications in Life Sciences - Yuriy L. Orlov (MDPI AG, 2021)
This Special Issue, “Life: Computational Genomics”, presents research articles on systems biology applications, computational genomics, and bioinformatics methods in life sciences [...]